Linear growth and systemic glucocorticoid therapy in children with systemic lupus erythematosus - Dikahayu Alifia Anugrah; Suryono Yudha Patria; Cahya Dewi Satria (Indonesian Pediatric Society, 2022)
Background The use of long-term oral glucocorticoid therapy, specifically in the treatment of systemic lupus erythematosus (SLE), has increased in the past two decades. Chronic glucocorticoid use may lead to a linear growth disturbances. Objective To determine the association between linear growth and systemic glucocorticoid therapy in pediatric SLE patients. Methods This retrospective cohort study used medical record data of pediatric SLE patients. All subjects received systemic glucocorticoids. The linear growth parameters recorded in this study were height-for-age z-score (HAZ) and height velocity at 0, 6, and 12 months of treatment. We recorded potential risk factors of linear growth disturbance, such as pubertal status, sex, SLE severity, pulse methylprednisolone use, daily glucocorticoid dose, and nutritional status. Results Of 42 patients with SLE, 83.3% were female, with a mean age of 13 years at diagnosis. Eighteen subjects (42.9%) experienced abnormal height velocity. There was a significant reduction in HAZ between 0, 6, and 12 months of treatment (P=0.016). Between 0 and 6 months of treatment, there was a mean HAZ decrease of 0.11 (P=0.015). There was a trend towards a risk for decreased HAZ at 6 and 12 months of treatment with pulse methylprednisolone (RR 1.25 and 1.27, respectively), as well as for abnormal height velocity (RR 1.73), but they did not reach statistical significance. Conclusion There is a reduction in linear growth in the first 12 months of systemic glucocorticoid therapy in children with SLE. Administration of systemic glucocorticoid significantly reduced HAZ in the first six months of therapy.